Clinical and Neurological Disorders in Systemic Vasculitis in Children - Iskanova G. Kh.; Egamova S. Sh. (Central Asian Journal of Medical and Natural Science, 2023)
The article describes the features of clinical and neurological changes in systemic vasculitis. 14 children with various forms of systemic vasculitis were examined. Systemic vasculitis was more common in girls. Pronounced changes in the nervous system were found in children with aortoarteritis.